Exploiting In-Vitro Culture systems for a wide rice gene pool (2006)
A successful rice breeding program depends largely on the degree of variability for important traits in the gene pool. In this study, we used different in-vitro culture (IVC) systems, anther (AC), seed (SC) and inflorescence culture (IC), to induce variations in the popular variety IR64. The AC-derived lines from IR64 were subjected to a second round of tissue culture using anthers, mature seeds and young inflorescences as explants. Plants were regenerated from the different tissue-culture systems. Breeding lines were developed from these regenerants through a series of evaluations. Variants for different traits were identified. Variability in plant height, heading date, maturity, tiller production and grain yield were observed. Planting season had its effect on the expression of these traits. Breeding lines taller and shorter, early and late heading/maturing, with more and fewer productive tillers, with higher and lesser grain yields than with seed derived (SD) IR64 were obtained. The extent of genetic variability differed with tissue culture system . In general, IC exhibited the greatest degree of phenotypic variability in most traits followed by AC and SC (IC>AC>SC). The same order applies to the relative proportions of the breeding lines with positive mutations, that is, better performers than SD IR64 in most traits evaluated. The mutations observed are randomly distributed among the genotypes/breeding lines generated from the three IVC systems and their expression was influenced by season. Subjecting IR64 to a second cycle of IVC yielded 82 lines that have either I to R reactions to BLB race 3 or 6, and 24 lines, with either I or R reaction to blast. Furthermore, 47 lines with moderate tolerance to salt stress were obtained. This has widened the adaptability of IR64. We now have IR64-derived lines which may be cultivated and perform better in salt-stressed areas. Results of this study have demonstrated the potential of the three IVC systems in broadening the rice gene pool, indicating further utilization for a successful rice breeding program.
Keywords: Rice breeding; Rice--Genetics